Estudo prospectivo e exploratório sobre as cachaças de alambique de Alagoas e suas potencialidades para a Indicação geográfica e seus diferenciais competitivos - Fonsêca, Liliane dos Santos Mota da (2020)
This research aims to present a prospective and exploratory study on the still cachaças in Alagoas, aiming at the geographical indication and its competitive differentials. It is known that Brazilian cachaças bring with them the history and origin of a people, when associated with the sugar and alcohol production of the State of Alagoas and the Era of colonization, the history of a people solidifies and rescues tradition and socio-cultural values, showing the region. As a result, cachaças from alembic in Brazil are of significant importance for the country, since their expressed genuineness, adds value and wealth to Brazilians, as well as moves the creative economy to discover a new vocation for the region. Over the years, Cachaças has gained strength in the universe of fine spirits, driving greater visibility of the product in the global market scenario. The granting of the IG - Geographical Indication comes to add, along with the peculiar aspects that occur with the indication of the origin of a product, making it typically valued. In Alagoas, the history of cachaça is confused with the traditionalism and culture of its people, since sugar mills draw the origin and formation of a society, which until then, depended on Pernambuco. So, the sugar cane spirit starts to take on a popular taste, and the distillate begins to compose very fine tastes for those who know and appreciate drinks of the highest quality. With that, Alagoas stills start to develop differentiated products for the market, with high competitive potential, very sensory values, translated into presentation and flavor, thus the geographical indication continues and strengthens the process of notoriety of the Cachaças de Alambique de Alagoas. The study found immeasurable gains, such as the feeling of belonging of a people given to the rescue of a rich history.